Loss of Adam10 Disrupts Ion Transport in Immortalized Kidney Collecting Duct Cells. Issue 4 (10th May 2021) - Assmus, Adrienne; Mullins, Linda; Ward, Mairi; Dobie, Ross; Hunter, Robert; Henderson, Neil C; Mullins, John J
Abstract: The kidney cortical collecting duct (CCD) comprises principal cells (PCs), intercalated cells (IC), and the recently discovered intermediate cell type. Kidney pathology in a mouse model of the syndrome of apparent aldosterone excess revealed plasticity of the CCD, with altered PC:intermediate cell:IC ratio. The self-immortalized mouse CCD cell line, mCCDcl1, shows functional characteristics of PCs, but displays a range of cell types, including intermediate cells, making it ideal to study plasticity. We knocked out Adam10, a key component of the Notch pathway, in mCCDcl1 cells, using CRISPR-Cas9 technology, and isolated independent clones, which exhibited severely affected sodium transport capacity and loss of aldosterone response. Single-cell RNA sequencing revealed significantly reduced expression of major PC-specific markers, such as Scnn1g (γ-ENaC) and Hsd11b2 (11βHSD2), but no significant changes in transcription of components of the Notch pathway were observed. Immunostaining in the knockout clone confirmed the decrease in expression of γ-ENaC and importantly, showed an altered, diffuse distribution of PC and IC markers, suggesting altered trafficking in the Adam10 knockout clone as an explanation for the loss of polarization. Graphical Abstract: